Fitting models to biological data using linear and nonlinear regression - Motulsky, Harvey (Oxford University Press, 2004)
Most biologists use nonlinear regression more than any other statistical technique, but there are very few places to learn about curve-fitting. This book, by the author of the very successful Intuitive Biostatistics, addresses this relatively focused need of an extraordinarily broad range of scientists